STRATEGI KOMUNIKASI PEMASARAN KOPI JANJI JIWA DI ERA DIGITAL DAN ERA PANDEMI COVID-19 - Mayang Riyantie; Alamsyah Alamsyah; Iswahyu Pranawukir (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Kopi Janji Jiwa is a fast-growing coffee shop chain in Indonesia. This research was motivated by external obstacles to the level of sales of the Promised Soul coffee caused by the Covid-19 pandemic. This is what makes one of the soul's promise coffees engaged in the coffee shop setting up marketing communication strategies during the Covid-19 pandemic. By using marketing communication strategies and theories and qualitative descriptive methodologies as well as non-participant observation techniques and in-depth interviews, it is found that the research results of Kopi Promise Jiwa maximize marketing communication strategies through digital strategies by carrying out the concept of PENCILS (Publications, Events, News, Community Involvement, Identity). Media, Lobbying and Social Investment) and digital media strategy. The results of the study found that in Publications Kopi Janji Jiwa conveyed a lot of information through its social media. Events are held consistently once a month with a different theme. News or news conveyed by Kopi Janji Jiwa to the mass media are also often seen in digital traces on search engines. The community found for the soul's promise coffee is often called #Temansejiwa. Media identity is carried out in the form of applying the image in each of the attributes used in its products. Lobbying and social investment are carried out in connection with promotions carried out by Kopi Promise Jiwa and other social activities.